Studi Evaluatif RGEC terhadap Stabilitas Keuangan PT Bank Panin Tbk Periode 2014–2024 - Dede Kurniasih; M. Yusuf; Afrizawati Afrizawati (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to evaluate the soundness of PT Bank Panin Tbk during the 2014–2024 period using the RGEC method, which assesses four key dimensions: risk, governance, earnings, and capital. This research approach is quantitative and descriptive, utilizing secondary data sourced from annual reports, financial statements, and officially published corporate governance documents. Each component is analyzed using relevant indicators, such as the NPL ratio, LDR, PDN, ROA, ROE, BOPO, NIM, and CAR. The results indicate that PT Bank Panin Tbk's risk profile, as reflected in the NPL, PDN, and LDR ratios, is largely in the healthy category, demonstrating the bank's ability to effectively manage credit and liquidity risks. An evaluation of corporate governance, based on consistent self-assessment reports over ten years, also demonstrates the achievement of a healthy rating, reflecting the bank's commitment to maintaining the principles of transparency, accountability, and regulatory compliance. Regarding earnings, profit performance, as measured by ROA, ROE, BOPO, and NIM, shows stable and positive results, confirming the bank's ability to generate sustainable profits. Meanwhile, in terms of capital, the CAR ratio recorded excellent performance and was a dominant factor in maintaining capital resilience while meeting the capital adequacy standards set by regulators. These findings confirm that PT Bank Panin Tbk was in overall good health throughout the study period. The results of this study are expected to provide strategic input for bank management in maintaining positive performance and for regulators as material for evaluating banking policies.